DASMA “ARNAUTE” (“GREKO-SHQIPTARE”) NË RAJONIN E DETIT AZOV (MATERIALET E STUDIMEVE SHKENCORE NË TERREN TË VITEVE 2015-2017) - Novik, Alexander A (Seminari Ndërkombëtar për Gjuhën, Letërsinë dhe Kulturën Shqiptare, 2017)
Ethnolinguistic and anthropological fieldwork in Rostov on Don region (village Margaritovo) was organized in 2015-2017. The materials of these expeditions are focused on ethnic culture and family rites of the local population in the border of Russia and Ukraine. The collected data of wedding traditions and revitalization of old rites are very important for the multidisciplinary study of the migrants from the Balkans (Arnauts, or Greeks and Albanians, according to historical archives of the 18th century) on the territory of the Russian Empire. Marriage is one of the main events that drastically change not only the life of the bridal couple, but also that of their families and relatives, of the whole local community, and in some cases even that of the wider circle of relatives and the region. The ethnographic data collected during fieldwork help the author to reconstruct the performative code of wedding rites by describing in detail the succession of wedding actions in the 1940s – 2010s regarded by reliable interlocutors as being most “traditional and Greek”.